MANAJEMEN PENGEMBANGAN USAHA EKONOMI PESANTREN: (Studi Kasus Di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo) - Imam Syafi'i; Wisri Wisri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
The Successful economic of management business development has some factors that can support to organizing and controlling in economic business of Boarding Institutions Salafiyah Syafi'iyah Sukorejo Situbondo. Researcher can find these from two operational methods, such as the study design and qualitative approach who has a role of key instrument. To get validity obtainded data, researcher used triangulation method by several steps. Such as data analysis, researcher known that economic management of business development in Boarding Institutions Salafiyah Syafi'iyah Sukorejo of Situbondo has some steps which are the organization that coordinating by an institution named Badan Usaha Milik Pesantren and the controlling one that held by the institution named Badan Pengawas Keuangan & Kekayaan Ma’had. Human Resources have an important thing to reach the successful of these situation. Based on the result of research, researcher can be gave the suggestion that we must increase the management system and controlling with professional act, autonomy expansion in management system, and providing training with brings someone experts from outside who are competent in the business world.